Modal Sosial Kognitif dalam Pengelolaan Parak dan Rimbo di Sumatera Barat - Ferdinal Asmin (Jurnal Psikologi Islam dan Budaya, 2020)
The cognitive elements of social capital need to be elaborated to understand the community-based forest management, such as the practice of parak and rimbo in the Koto Malintang and Simancuang communities. This study aims to identify and describe these cognitive elements. The research method used was case study method with constructivism paradigm. The data was collected using interview, observation, and document review techniques. Cognitive social capital can be developed through local ecological knowledge that has become part of Minangkabau customs and culture. The results showed that cognitive elements in the form of norms, values, beliefs and attitudes can describe how the community plans, utilizes, and controls the forest resource management. The identification of these cognitive elements shows that people pay attention to the principles of sustainability, justice, ability, security, profit, opportunity, and well-being.